1995
DOI: 10.1111/j.1527-2001.1995.tb01355.x
|View full text |Cite
|
Sign up to set email alerts
|

“Male-Order” Brides: Immigrant Women, Domestic Violence and Immigration Law

Abstract: This essay analyzes why women whose immigration status is dependent on their marriage face higher risks of domestic violence than women who are citizens and explores the factors that collude to prevent acknowledgment of their greater susceptibility to battering. It criticizes elements of current U.S. immigration policy that are detrimental to the welfare of battered immigrant women, and argues for changes that would make immigration policy more sensitive to their plight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 2 publications
2
90
0
Order By: Relevance
“…For instance, welfare offices across the country have provided little support to domestic violence victims who are unable to meet welfare work requirements because of the abuse (Levin, 2001;Lindhorst & Padgett, 2005;Postmus, 2004). In this way, the economic context of victims' lives and the structure of the social welfare system's response also affect the impact of IPV and the options available to victims.The experience of IPV for immigrant women in the United States must also be understood in the context of their immigration status and the context of oppressive anti-immigrant policies (Chang, 2000;Narayan, 1995;Shetty & Kaguyutan, 2002). Immigration status varies across and within cultural groups (Yoshihama, 2001), with significant implications for victims of IPV.…”
mentioning
confidence: 99%
“…For instance, welfare offices across the country have provided little support to domestic violence victims who are unable to meet welfare work requirements because of the abuse (Levin, 2001;Lindhorst & Padgett, 2005;Postmus, 2004). In this way, the economic context of victims' lives and the structure of the social welfare system's response also affect the impact of IPV and the options available to victims.The experience of IPV for immigrant women in the United States must also be understood in the context of their immigration status and the context of oppressive anti-immigrant policies (Chang, 2000;Narayan, 1995;Shetty & Kaguyutan, 2002). Immigration status varies across and within cultural groups (Yoshihama, 2001), with significant implications for victims of IPV.…”
mentioning
confidence: 99%
“…For immigrant women two of the primary concerns that were raised by the participants who had an understanding of these complexities were fear of deportation and lack of services in the language of the DV survivor. Some studies have indicated that the rates of abuse for immigrant women have been reported to be as high as 77% as compared to the range given for U.S. citizens of 12-50% (Narayan, 1995). Immigrant women face a set of issues such as having their legal immigration status dependent upon their marriage to a U.S. citizen or Legal Permanent Resident, and linguistic and financial dependence on their spouse.…”
Section: Citizenshipmentioning
confidence: 99%
“…Safety issues for women who report DV to the police, fear of deportation, and the sense of responsibility for the continued disintegration of the community may all be reasons to avoid involvement in the issue of DV (Ferraro, 1996;INCITE, 2006;Narayan, 1995) One participant described the complexity of the issue:…”
Section: Reaching Out In the Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Further concealing endemic violence and abuse of women are state centric pohcies and laws, implemented and interpreted to the exclusion of women's interests (Pettman 1996ab;Truong 1990;Peterson and Runyan 1999;Narayan 1995;Connell 1987Connell , 1994Steinstra 1996Steinstra ,1994.…”
Section: The Trafrcking Prorteersmentioning
confidence: 99%